Volume 4: Heat Transfer, Parts a and B 2012
DOI: 10.1115/gt2012-69117
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Coolant Density on Turbine Blade Film-Cooling With Compound-Angle Shaped Holes

Abstract: Adiabatic film-cooling effectiveness is examined systematically on a typical high pressure turbine blade by varying three critical flow parameters: coolant blowing ratio, coolant-to-mainstream density ratio, and freestream turbulence intensity. Three average coolant blowing ratios 1.0, 1.5, and 2.0; three coolant density ratios 1.0, 1.5, and 2.0; two turbulence intensities 4.2% and 10.5%, are chosen for this study. Conduction-free pressure sensitive paint (PSP) technique is used to measure film-cooling effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…22). However, Liu et al (2012) reported that the density ratio effect on turbine blade film cooling with compound angled shaped-hole (see Fig. 21) is not as significant as that with compound angled cylindrical hole reported by Narzary et al (2012).…”
Section: Fig 23mentioning
confidence: 82%
See 2 more Smart Citations
“…22). However, Liu et al (2012) reported that the density ratio effect on turbine blade film cooling with compound angled shaped-hole (see Fig. 21) is not as significant as that with compound angled cylindrical hole reported by Narzary et al (2012).…”
Section: Fig 23mentioning
confidence: 82%
“…Blades with leading-edge film-cooling array and suction-side film cooling were Fig. 21 Details of the test film-cooled blade with shaped cooling holes on the pressure and suction surfaces studied by studied by Liu et al (2012).…”
Section: Work In 1980smentioning
confidence: 99%
See 1 more Smart Citation